Proses Pembuktian dan Penggunaan Alat-Alat Bukti Pada Tindak Pidana Pertambangan Tanpa Izin Pada Perusahaan - Islah, Islah; Magdalena, Ely (Legalitas: Jurnal Hukum, 2023)
Investigation was an important part the phase criminal justice to decide crimes in the field of mining minerals and coal, As through investigation , investigators can do serangkaiam the act of to gather evidence can make light of an event criminalwho has been happened so that through evidence collected in carefully and thoroughly can be found suspects crimes mining minerals and coal. Verifiable are only some of the criminal law governing macam-macam legal evidence, the system adopted in kind, syarat-syarat and procedures present any location andthe authority of a magistrate to receive, refuse and assess a verifiable.The legal basis of the criminal evidence in law based on article 183-189 KUHAP and Evidence any that applied and arranged in kuhap indonesia based on article 184 paragraph ( 2 ) is: a witness, the people of the information, a letter, guidance,information the defendant. Evidence any either on of evidence of a criminal act in indonesia, both those which have arranged in special laws and still based on pure kuhap of course make an impact progress for the enforcement of law inIndonesia